2010
DOI: 10.2975/34.2.2010.130.136
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery Education in the Academy Program: Transforming academic curricula with the principles of recovery and self-determination.

Abstract: REAP has delivered state-of-the-science education to over 1,000 trainees, including medical students, psychiatry residents, psychology and social work interns, and rehabilitation counselors, pre/post-doctoral students and professionals within a variety of academic settings. REAP serves as a replicable structure to successfully integrate recovery education into existing, accredited academic programs and curricula using the parameters outlined by multiple experts and stakeholders. Barriers to curricular transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…(Psychiatric Services 64:1211-1217, 2013; doi: 10.1176/appi. ps.201200546) M ental health care continues to move toward recoveryoriented, consumer-directed services (1)(2)(3)(4). Central to this transformation are services that promote self-determination and mental health care-related activation, hope, and belief in recovery; are based on respect; and recognize that individuals have different needs, preferences, goals, and recovery pathways (1).…”
mentioning
confidence: 98%
“…(Psychiatric Services 64:1211-1217, 2013; doi: 10.1176/appi. ps.201200546) M ental health care continues to move toward recoveryoriented, consumer-directed services (1)(2)(3)(4). Central to this transformation are services that promote self-determination and mental health care-related activation, hope, and belief in recovery; are based on respect; and recognize that individuals have different needs, preferences, goals, and recovery pathways (1).…”
mentioning
confidence: 98%
“…The literature on mental health recovery contains information on the knowledge and attitudes of mental health professionals including social workers (Carpenter ,2002;Clearly & Dowling, 2009;Scheyett et al, 2009), psychiatrists (Peebles et al,2009;Razzano et al, 2010;Stratford, Brophy, & Castle,2012), and psychologists (Clearly& Dowling, 2009;Peebles et al,2009;Reddy, Spauldin, Jansen, Menditto, & Pickett, 2010) but contains little information about counselors. There is a continued discussion about how mental health professionals can support consumer recovery, as mental health professionals can have positive or negative effects on consumer recovery (Berry & Greenwood, 2015;Wilrycx, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains studies about mental health recovery and the knowledge and attitudes of mental health professionals including social workers (Carpenter ,2002;Clearly & Dowling, 2009;Scheyett, DeLuca, & Morgan, 2009), psychiatrists (Peebles et al,2009;Razzano et al, 2010;Stratford, Brophy, & Castle,2012), psychologists (Clearly& Dowling, 2009;Peebles et al,2009;Reddy, Spauldin, Jansen, Menditto, & Pickett, 2010), and counselors (Crowe et al, 2013). Clearly and Dowling's (2009) study found that nurses, doctors, social workers, occupational therapists, and psychologists indicated an adoption of the recovery model in the delivery of professional services; however, the nurses, doctors, social workers, occupational therapists, and psychologists were limited in their knowledge of essential aspects of recovery.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…I opplaeringsprogrammet for familieterapeuter vektlegges det hvordan de i samtaler med familier kan fremme recoverybaserte relasjoner og samarbeid, utforske muligheter i bedringsprosesser, planlegge og organisere disse samt bidra til at nødvendige ressurser kan benyttes i samarbeidet. Razzano, Jonikas, Goelitz, Hamilton, Marvin, Jones-Martinez & Cook (2010) beskriver et studium gjennomført ved University of Illionis, Chicago's National Research and Training Center on Psychiatric Disability. Studieprogrammet er omtalt som REAP (Recovery Education in the Academy Program).…”
Section: Opplaeringsprogrammer For Ansatteunclassified